Comparison between measurement of sodium and potassium by Blood Gas Analyzer versus Laboratory based Auto-analyzer among critically ill patients in a tertiary care hospital - Khan, Nazia Nusrat; Mahiyuddin, Najeeb; Ahsan, ASM Areef; Fatema, Kaniz; Ahmed, Fatema (Bangladesh Critical Care Journal, 2023)
Background: Electrolytes imbalances can lead to critical life threatening events so immediate and accurate assessment is needed. There is always a time delay in receiving results from the central laboratory auto analyzer (AA). To overcome this drawback, arterial blood gas (ABG) analyzer can be used as an alternative to measure electrolytes where results can be obtained within two minutes, allowing for prompt management. Methods: This cross-sectional study was carried out on 384 intensive care unit (ICU) patients of Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic disorders (BIRDEM) General Hospital. The average values of sodium and potassium in ABG analyzer and laboratory AA were calculated and then the mean difference or bias was obtained of sodium and potassium measurements analyzed by the two methods. Bland-Altman plot and Lin’s concordance correlation coefficient (ρc) was used to measure the agreement between the two methods. Test results were considered reliable, if the bias was non-significant and within the United States Clinical Laboratory Improvement Amendment (US CLIA) criteria (±4 mmol/l for sodium and ±0.5 mmol/l for potassium), 95% limits of agreement (LOA) were narrow and ρc showed good concordance. Results: The mean difference or bias, 95% LOA and ρc for sodium was -1.2 mmol/l, -11 mmol/l to 8.6 mmol/l and 0.85 respectively whereas for potassium this was 0.8 mmol/l, -0.39 to 1.98 mmol/l and 0.63 respectively. The bias for sodium was within the US CLIA criteria but not so for potassium. However, the 95% LOA was wide and there was poor concordance for both the measurement. On account of these differences, correction factor was calculated for sodium and potassium values. Serum sodium (in mmol/l) was 2.48 + 0.97 x ABG sodium (in mmol/l) and serum potassium (in mmol/l) was 1.18 + 0.89 x ABG potassium (in mmol/l). Conclusion: The sodium and potassium measurements obtained from the ABG analyzer was found to be unreliable. However, a correction factor to the ABG analyzer results could be applied to initiate treatment and then changing the management, if required, once laboratory AA reports become available. Bangladesh Crit Care J March 2023; 11 (1): 3-8